The Portail Royal of Chartres: Historiography and Iconography (Fenestella. Inside Medieval Art, 2020)
Concerning the Portail Royal of Chartres: Historiography and IconographyThis article aims to survey the historiography on the three sculpted tympanums of the Portail Royal of Chartres Cathedral, which represents an essential context of the early Gothic. From the contribution of Hénault (1876) to the fine-tuning of Christe (2013), Angheben (2017) and Berné (2018), the studies have encountered many difficulties, especially concerning the central and left tympanums.Scholars faced a debate full of articulations and clarifications, from Emile Mâle (1948) to Adolf Katzenellenbogen (1959), from Willibald Sauerländer (1972 and 1984) to Margot Fassler (1993 and 2010), from Anne Prache (1993 and 2000) to Eliane Vergnolle (2008), from Roland Halfen (2001) to Till Evers (2011 and 2012), from Yves Christe (2013) to Marcello Angheben (2017). The attempts to recognise in the left tympanum a subject other than the Ascension (Van der Meule 1981, Fassler 1993) were unsuccessful, and Fassler herself then changed her position.More singular, until recently, is the substantial misunderstanding of the iconography of the central tympanum, which in no way can assume eschatological connotations. It is instead a present vision of Christ's majesty, and the Apostles with books and rotuli do not appear as assessors of the Last Judgement, but rather as entrusted with the mission of evangelisation: they represent the earthly Church that must complete the mission in this world (Mk 16, Mt 24). An Author's contribution on this tympanum is being published.
Keywords: Iconography; Chartres; Book of Revelation; Maiestas Domini; Apostels; Gothic Sculpture; Portail Royal